Parenting education and social pedagogy: evaluation an intervention proposal - Garcia, Narjara Mendes (2016)
Parenting educational interventions are rare in Brazil and relate to the field of social pedagogy. This proposal presents the analysis of a proposal on a family educational program for the promotion of responsible parenting. Therefore, a parenting educational european program was conducted in a Brazilian context entitled “Growing as a Happy Family”. It was investigated: the dynamics of operation, the role of the facilitators, the satisfaction/ effectiveness in the view of the team of educators and the participating families. The results indicated a need to guarantee the adherence/participation of families and some adjustments to the Brazilian context. The elements that mostly contributed to the satisfaction/effectiveness of the parenting educational program in Brazil were the quality of pedagogical mediation of the educators with the families, the systemic approach to the educational proposal content and the use of methodologies of Social Pedagogy that are based on dialogue and respect to the individual and cultural differences.